2009
DOI: 10.1055/s-0029-1243201
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Arachnoiditis and Thecaloscopy: Brief Review and Proposed Treatment Algorithm

Abstract: The term arachnoiditis describes the inflammation of the meninges and subarachnoid spaces. Lumbar arachnoiditis is characterized by obliterated nerve root sleeves and the adherence of nerve roots to each other in the proximity of the cauda equina, and may be secondary to infectious diseases or tumors, iatrogenic (subsequent to spinal surgery) or idiopathic. It is not very clearly defined epidemiologically or clinically, and various theories regarding its pathophysiology have been proposed; furthermore, its tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…1 , 2 ). Nerve conduction studies and electromyography can differentiate the disease from other forms of polyneuropathy, especially when there is no motor involvement [ 5 ]. Unfortunately, nerve conduction studies were not available at the time of this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 , 2 ). Nerve conduction studies and electromyography can differentiate the disease from other forms of polyneuropathy, especially when there is no motor involvement [ 5 ]. Unfortunately, nerve conduction studies were not available at the time of this study.…”
Section: Discussionmentioning
confidence: 99%
“…There have been other reports of subarachnoid hemorrhage, myelographic contrast agents, degeneration of the spinal cord, genetic fibrinolytic defects, and keloid-like scarring [ 3 , 4 ]. In some rare instances, no specific cause can be demonstrated leading to conceivable diagnoses such as mechanical irritation, undiagnosed TB, or an aseptic inflammation [ 5 ]. TB arachnoiditis should be considered in endemic regions especially when no other obvious cause is found [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…These surgical options include thecaloscopy, neural stimulation, arachnoidolysis, flexible endoscopy, and subarachnoid-subarachnoid shunting. [11][12][31][32][33] These surgical techniques have shown short-term improvements in pain, although most patients returned to baseline or worsened in the long term. 1,12,33 Our patient is a prime example of a failed response to multiple lumbar spine surgeries with little impact on her neurologic deficits, pain status, and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of improved flexibility and optic technology in the endoscope have allowed further applications beyond the brain through clear inspection without injury to surrounding brain areas. In 2001, Warnke et al suggested the use of flexible endoscopes as thecaloscopes for thecaloscopy, a procedure for viewing the lumbar thecal sac and the spinal canal, and proposed the use of the procedure for the treatment of arachnoiditis, spinal arachnoid cysts, and intraspinal meningocele (40,(86)(87)(88).…”
Section: Improvement Of Endoscopic Instrumentmentioning
confidence: 99%